2021
DOI: 10.1080/01402382.2021.1917154
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing, politics and wealth

Abstract: Since the beginning of the COVID-19 epidemic, governments across Europe have attempted to prevent the spread of the disease by limiting the movement of their citizens. In this article, we analyse whether the level of compliance with social distancing measures is associated with political, economic, and demographic factors. In particular, our interests lie in two areas. First, as lockdowns have dragged on, many countries see some political resistance, often, though not always, from populist movements: are local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Moreover, public trust matters directly for public-health policy, since it increases adherence to the advice of public health authorities and compliance with laws and regulations (Im et al 2014;Marien and Hooghe 2011). As also shown in other contributions in this special issue, public approval depends on trust in national leaders (Altiparmakis et al 2021), and compliance with the advice of health authorities on things like social distancing depends on populist political attitudes and the feeling of economic security (Ansell et al 2021). To our knowledge, our article is the first study that compares public opinion and political trust in Sweden and Denmark over time during the COVID-19 pandemic, although the comparison has been made many times in political commentary, media coverage, and think-tank reports.…”
mentioning
confidence: 71%
“…Moreover, public trust matters directly for public-health policy, since it increases adherence to the advice of public health authorities and compliance with laws and regulations (Im et al 2014;Marien and Hooghe 2011). As also shown in other contributions in this special issue, public approval depends on trust in national leaders (Altiparmakis et al 2021), and compliance with the advice of health authorities on things like social distancing depends on populist political attitudes and the feeling of economic security (Ansell et al 2021). To our knowledge, our article is the first study that compares public opinion and political trust in Sweden and Denmark over time during the COVID-19 pandemic, although the comparison has been made many times in political commentary, media coverage, and think-tank reports.…”
mentioning
confidence: 71%
“…In Britain, compliance with rules mandating staying at home and social distancing has been found to be more prevalent among low socio-economic households (Smith et al, 2020;Fancourt et al, 2021; see also footnote 21), while compliance with isolation rules has been found more prevalent among high socio-economic households (Smith et al, 2021). Levels of homeworking, along with the ability to work at home, have been found to be greater among high income groups than among low income groups (Felstead and Reuschke, 2020;Ansell et al, 2021;Atchison et al, 2021), suggesting the costs of avoiding workplaces are lower for wealthier individuals.…”
Section: Datamentioning
confidence: 99%
“…Similar findings come from Barrios and Hochberg (2020), who show that the risk perception of COVID-19 is moderated by partisan bias. Concerned with European countries, Ansell et al (2021) show that regional populist support is correlated with reduced social distancing compliance.…”
Section: Literature Reviewmentioning
confidence: 95%